Dyslipidemia initiates keratinocytes proliferation through upregulation of lncRNA NEAT in psoriasis patients - Abeer Mostafa; Dina Sabry; Nesreen Aboraia; Ahmed Fawzy; Amany A. Abou-Elalla (Molecular Biology Reports, 2023)
Background Psoriasis is a chronic inflammatory immune-mediated and hyper proliferative skin disorder that has underlying genetic factors. Psoriasis can result from interaction of cytokines between keratinocytes and T-lymphocytes. NEAT is a lncRNA involved in immune modulation and has been previously studied in cancers. This study aims to clarify the unprecedented role of NEAT in psoriasis pathogenesis. Methods The study was conducted on 50 healthy control subjects and 50 psoriasis patients. Blood samples from all participants were collected for analysis of their lipid profile. qRT-PCR was done for lncRNA NEAT, TNF-α, VEGF genes expression. The levels of ROS and caspase-3 were estimated by ELISA. ROC analysis was done to detect the diagnostic value of lncRNA NEAT gene expression. Results Dyslipidemia is more prevalent among psoriasis patients. A significant up regulation in lncRNA NEAT, TNF-α, VEGF genes expression ( p value˂0.001) in psoriasis patients in addition to significant increase in ROS and caspase-3 levels ( p value˂0.001) in compare to controls. Additionally, a positive significant correlation between TNF-α, ROS, NEAT, caspase-3 and dyslipidemia. NEAT had an area under the curve (AUC) of 0.931 (95% CI 0.844–0.978, p < 0.001). Conclusion Dyslipidemia is an initiating signal in psoriasis pathogenesis that creates a state of chronic inflammation and oxidative stress. This state induces keratinocytes proliferation and release of NEAT with subsequent caspase-3 activation to counteract the proliferating cells. NEAT could be considered as a good diagnostic biomarker for psoriasis. Graphical abstract